2011
DOI: 10.1037/a0023589
|View full text |Cite
|
Sign up to set email alerts
|

Why do lie-catchers fail? A lens model meta-analysis of human lie judgments.

Abstract: Decades of research has shown that people are poor at detecting lies. Two explanations for this finding have been proposed. First, it has been suggested that lie detection is inaccurate because people rely on invalid cues when judging deception. Second, it has been suggested that lack of valid cues to deception limits accuracy. A series of 4 meta-analyses tested these hypotheses with the framework of Brunswik's (1952) lens model. Meta-Analysis 1 investigated perceived cues to deception by correlating 66 behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
456
5
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 469 publications
(493 citation statements)
references
References 82 publications
(168 reference statements)
21
456
5
11
Order By: Relevance
“…Some clients get defensive, or strain to maintain eye contact. This can be interpreted as overcompensating for the common assumption that those who deceive are unable to maintain eye contact (DePaulo et al, 2003), an attempt to dupe the listener by overly conforming to perceived cues of honesty, and other behavioural cues, though none of these behavioural actions are reliable cues to deception (Curtis & Hart, 2015;Hartwig & Bond, 2011;Mann, Vrij, & Bull, 2004). Looking away was believed to be an indicator of falsehoods by 64% of 11,157 subjects in a study involving people of various cultural backgrounds, even though it has not been found to be a reliable indicator of deception (Global Deception Research Team, 2006).…”
Section: Recognising Deception In Clinical Practicementioning
confidence: 99%
“…Some clients get defensive, or strain to maintain eye contact. This can be interpreted as overcompensating for the common assumption that those who deceive are unable to maintain eye contact (DePaulo et al, 2003), an attempt to dupe the listener by overly conforming to perceived cues of honesty, and other behavioural cues, though none of these behavioural actions are reliable cues to deception (Curtis & Hart, 2015;Hartwig & Bond, 2011;Mann, Vrij, & Bull, 2004). Looking away was believed to be an indicator of falsehoods by 64% of 11,157 subjects in a study involving people of various cultural backgrounds, even though it has not been found to be a reliable indicator of deception (Global Deception Research Team, 2006).…”
Section: Recognising Deception In Clinical Practicementioning
confidence: 99%
“…Regardless of lie or truth bias, overall accuracy of detection still remains at near chance. It is argued that one reason for detection inaccuracy is that people rely on stereotypical and incorrect indicators of deception such as lack of eye contact or fidgeting when judging honesty (Hartwig & Bond, 2011;The Global Deception Research Team, 2006;A Vrij, Davies, & Bull, 2008). Hartwig and Bond (2011) conducted a metaanalysis that found judges, despite their overall inaccuracy, perceived deception indicators accurately.…”
Section: Deception Detection By Humansmentioning
confidence: 99%
“…Another reason offered for inaccuracy is that deceptive behavioral cues may not occur often or strongly enough to be noticed during interactions (DePaulo et al, 2003;Hartwig & Bond, 2011). This is further complicated when considering IDT's prediction that behaviors indicating deception change over the course of the interaction and in response to the situational demands.…”
Section: Deception Detection By Humansmentioning
confidence: 99%
“…The ability to achieve this involves a multiple step process that can be illustrated by Brunswick's (1956) lens model (as described by Hartwig & Bond, 2011). According to the model, the phenomenon of lying must be studied in two main ways to develop sound methods to increase detection accuracy.…”
Section: Purported Versus Valid Cues Used To Detect Deceptionmentioning
confidence: 99%
“…Among those who suffer such consequences are innocent people who are wrongly convicted of crime due to false claims of their guilt. Numerous empirical studies have been conducted to improve efforts at lie detection (see DePaulo et al, 2003;Hartwig & Bond, 2011), most of which have focused on detecting deception in suspects' confessions to crime (e.g., Kassin & Gudjonsson, 2004) or denials of involvement in crime (e.g., Strömwall, Granhag, & Jonsson, 2003). However, relatively little research attention has been paid to the veracity of crime reports made by those other than suspected and actual perpetrators.…”
Section: Introductionmentioning
confidence: 99%